Public Financial Management in the Health Sector in Malawi : Opportunities to Strengthen Service Delivery at the Local Level - World Bank (World Bank, Washington, DC, 2021)
Health outcomes in Malawi have improved significantly, largely due to improvements in access and quality. Despite adverse macro-fiscal conditions, fiduciary concerns, and donors shifting funding toward off-budget financing modalities, there has been a huge improvement in service delivery over the past two decades. Improving the way government funds are spent in Malawi is paramount. Evidence shows that the quality of public financial management (PFM) significantly affects service provision and health outcomes. To assess the extent to which the PFM system in Malawi supports health service delivery, a study was undertaken in six districts focusing on health centers and hospitals. A total of 95 interviews were undertaken with officials from all six district councils and district health offices; 10 hospitals; and seven health centers. This policy brief draws on this study identifying PFM gaps and constraints at the local level, as well as critical areas for action. These findings and recommendations are expected to support decision makers and practitioners with ongoing public financial management reforms.